Identification of Vulnerable Areas to Maritime Tourists on The Coast of Pacitan Regency (EarthCare, 2022)
The Pacitan Regency is renowned for having stunning beaches with panoramic views that can attract tourists. The Pacitan Regency is home to several marine tourism hotspots, including Banyutibo Beach, Buyutan, Ngiroboyo, Pidakan, and Seruni. However, there may be a threat to tourists lurking behind the stunning view of the beaches that directly face the Indian Ocean. Therefore, this study aimed to assess marine hazards based on coastal characteristics in marine tourism destinations in Pacitan Regency through geomorphological approaches, remote sensing, map analysis, and secondary data from agencies, as well as to formulate recommendations for minimizing marine hazards. The collected data were then processed to obtain information on the characteristics of beaches in marine tourism areas and information on marine hazards. This information was then used as the basis for the preparation of marine hazard mitigation recommendations. Based on the results, it was determined that Banyutibo, Ngiroboyo, and Seruni Beaches had all possible marine hazards. Meanwhile, Buyutan Beach experienced both a tsunami sea hazard and extreme waves, whereas Pidakan Beach only had a tsunami sea hazard. Although hacking currents do not occur on all Pacific beaches, the intensity of their occurrence is the most common among other marine hazards in marine tourism areas. Mitigation efforts must be carried out by building cooperation from all parties to reduce the impact of losses due to marine accidents, such as the installation of Marine Hazard Maps, the installation of prohibition signs, socialization, and education about reducing the risk of marine hazards to the community, etc.